Higher Serum Brain-Derived Neurotrophic Factor Levels Are Associated With a Lower Risk of Cognitive Decline: A 2-Year Follow Up Study in Community-Dwelling Older Adults - Fujiwara, Yoshinori; Ihara, Kazushige; Hachisu, Mitsugu; Suzuki, Hiroyuki; Kawai, Hisashi; Sakurai, Ryota; Hirano, Hirohiko; Chaves, Paulo H. M.; Hashizume, Masahiro; Obuchi, Shuichi (Frontiers in Behavioral Neuroscience, 2021)
Objective: To examine the relationship of serum brain-derived neurotrophic factor (BDNF) levels with subsequent short-term decline in cognitive functioning of community-dwelling older adults. Design: Two-year prospective, observational study Setting and Participants: Four hundred five adults aged 65-84 years, living in an urban city (Tokyo, Japan). Methods: Participants free of a dementia diagnosis underwent health assessments at baseline (2011) and follow-up (2013). Serum BDNF levels and scores from the Montreal Cognitive Assessment-Japanese version (MoCA-J) were measured systematically. Logistic regression was used to assess the odds of cognitive decline between baseline and follow-up visitsin the full MoCA-J scale (operationally defined as a decrease of 2 or more points), as well as in MoCA-J subscales (decline of 1 or more points in a specific subscale), as a function of serum BDNF level, adjusting for baseline demographics, prevalent chronic diseases, and baseline cognitive scores. . Results: Among individuals who performed worse on the full MoCA-J at baseline (i.e., scores in the bottom quartile [≤21], which is consistent with a mild cognitive impairment status), but not among those who performed better (top 3 quartiles), those with highest baseline serum BDNF levels (top quartile) had lower odds of subsequent decline in the full MoCa-J scale than those with lowest (bottom quartile); i.e., OR): .10 (95% CI: .02-.62; p=.013). Regarding MoCA-J subscales, adjusted odds of decline in the executive function subscale, but not in the other 5 subscales, were substantially lower among those with highest baseline serum BDNF levels (top quartile), as compared to those with lowest (bottom quartile); i.e., odds ratio (OR): .27 (95% confidence interval [CI]: .13-.60; p<.001). Conclusions and Implications: Higher serum BDNF levels were associated with lower risk of decline in cognitive function in a sample of community-dwelling older Japanese adults. Risk varied among cognitive subdomains and according to baseline cognition. Research seeking to evaluate the added-value of serum BDNF in health promotion initiatives directed towards cognitive decline prevention in community-dwelling older adults is warranted.